Perception of the population of São Gonçalo do Rio Abaixo (MG) about the socio-environmental and economic impacts caused by the explotation of iron ore in the Brucutu mine (Research, Society and Development, 2018)
Mining represents one of the pillars of the Minas Gerais state, given that the Quadrilátero Ferrífero corresponds to one of the most representative regions in the State's mineral exploration. However, this exploitation implies in environmental degradation, as well as negative impacts in the social and economic spheres. In view of this, this work aimed to verify the perception of the São Gonçalo do Rio Abaixo (MG) population about the socio-environmental and economic effects of the mining activity in the city. A questionnaire has been applied to 370 individuals from this community. Thus, in the perception of 79.7% of the respondents, the installation of mining enterprises in the municipality is important, with 30.8% of the participants affirming that the main positive impact is the generation of employment. However, in the view of 57.5% of the respondents the mining activity promotes soil degradation, water contamination, air pollution, and contribute to the loss of biodiversity. Given the importance of mining for the city's economy, it is necessary to monitor and conduct research on the impacts of mining exploration, seeking the promotion of actions in order to minimize their negative effects on the environment and the community.